The Role of Ethical Orientation and Moral Intensity in Improving Ethical Decision of An Auditor - Dewi Indriasih; Wiwit Apit Sulistyowati (Universitas Pendidikan Indonesia, 2021)
Abstract. Ethical decision making is an action expected to be performed by an auditor despite facing conditions involving an ethical dilemma. This study aims to examine the ethical decision of auditors through ethical orientation as well as the moral intensity owned by the auditor. This study was conducted at the Auditor Inspectorate in Tegal City with a census sampling technique obtained 33 auditors as research respondents. Regression analyses are used to test the effect of ethical orientation and moral intensity on the ethical decisions of an auditor. Partial hypothesis testing results show that ethical and moral orientation affects the ethical decisions of Auditors. This study gives implications that with the ethical orientation and moral intensity of the auditors in conducting its function, the auditor will consider the ethical aspect to improve their integrity.Keywords: Ethical Decision; Ethical Orientation; Moral Intensity.Abstrak. Pengambilan keputusan etis adalah tindakan yang diharapkan dapat dilakukan oleh seorang auditor meskipun menghadapi kondisi yang melibatkan dilema etis. Penelitian ini bertujuan untuk menguji keputusan etis auditor berdasarkan orientasi etis dan intensitas moral yang dimiliki auditor. Penelitian ini dilakukan pada Auditor Inspektorat Kota Tegal melalui teknik sensus sampling diperoleh 33 auditor sebagai responden penelitian. Analisis regresi digunakan untuk menguji pengaruh orientasi etis dan intensitas moral terhadap keputusan etis auditor. Hasil pengujian hipotesis secara parsial menunjukkan bahwa orientasi etis dan intensitas moral berpengaruh terhadap keputusan etis auditor. Penelitian ini memberikan implikasi bahwa dengan orientasi etis dan intensitas moral, auditor dalam menjalankan fungsinya akan mempertimbangkan aspek etika untuk meningkatkan integritasnya.Kata Kunci:Keputusan Etis; Orientasi Etis; Intensitas Moral.